CULTURALLY RESPONSIVE TEACHING (CRT) APPROACH: TEACHING BIOLOGY IN A WETLAND ENVIRONMENT - Yulinda, Ratna (International Conference On Social Science Education, 2025)
This study aims to describe the design of Teaching Modules with a Culturally Responsive Teaching Approach on junior high school biology material in a wetland environment. This research is descriptive and qualitative. Data collection techniques used observation, interview and documentation techniques. Data analysis techniques involve data reduction, data presentation, and data verification. The results showed that the teaching modules prepared by prospective teacher students had met the standards for preparing teaching modules for the Merdeka Curriculum, which contained general information, learning outcomes, learning objectives, mapping learning objectives, learning materials, models, approaches, learning methods, media, learning tools, and learning resources. Student teachers have shown a good understanding of the key components in preparing teaching modules. The Culturally Responsive Teaching approach covers topics such as classification of living things, biotechnology, additives, and motion in plants. Teaching modules with this approach provide relevant examples for specific environments, encourage the development of more inclusive curricula, improve the quality of teaching, and provide prospective biology and science teachers with experience in designing lessons responsive to the wetland environment. In addition, this teaching module can serve as an example for other teachers.